HANDS-ON AND REMOTE LABORATORIES WITH ARDUINO FOR EVERYONE - LUSTIG, František (Trends in education, 2018)
The number of remote laboratories around the world seems to be stagnating or rather declining. The development of new real remote remote control laboratories is probably too complex and costly, it requires a permanent service, etc. In the paper we come up with an alternative solution that does not use professional measurement systems, but we will focus on the easily accessible Arduino board. Every beginner and non-programmer can build a remote experiment with Arduino and our freely downloadable software kit "Remduino Lab SDK".
Keywords: remote laboratories; Arduino; ISES